Introdução de veículos elétricos no alimentador JPS B-l6 - Sousa, Diógenes Montiel Rodrigues de (2023)
The introduction of Electric Vehicles is a reality in the world, due, among other factors, to the concern with the emission of pollutants from combustion engines. This load entry can generate some difficulties for electrical systems globally or regionally. Therefore, this document addresses a study on the impacts of Electric Vehicles on the Energisa JPS Bl-6 feeder, which was implemented using the Distributor’s Geographic Database. The system modeling is built in Simulink/MATLAB®, with time domain simulations. The analysis of impacts includes the capacity of the feeders, in terms of voltage and power, as well as the Load Factor. In addition, some solutions were suggested as a way of mitigating the impacts that the excess charge of Electric Vehicles would add to the demand of the feeder. One of these solutions will be analyzed in detail, in order to verify if it would bring satisfactory results and the investment would be worthwhile. Thus, the aim is to perform energy management with the introduction of the Battery Bank in the feeder so that it works as an auxiliary service of the system.